The Effects of Stake Priming and Planting Method on Early Growth of Cassava Grown under Greenhouse Conditions - Polthanee, Anan; Bamrungrai, Jiraporn (Asian Health, Science and Technology Reports, 2016)
The objective of this research is to evaluate the effects of stake priming and planting position on shoot and root growth of cassava, and to improve planting material quality for the early crop establishment period. Three pot experiments were conducted with different bio-activators, soil moisture regimes, and genotypic variations. Results revealed that stake priming increased shoot and root growth of cassava at 21 days after planting (DAP). Stakes soaked in chitosan at a concentration of 10 ml, diluted in ten liters of water for two hours, showed to be the most effective priming method for improving stake quality. Soil moisture regimes applied once at planting at 10% by weight (tension 0.075 bars) and 20% by weight (tension 0.05 bars), had significant effect on root growth of cassava at 21 DAP. Root length and root dry weight were observed higher at 10% level than those of soil moisture at 20% level. Horizontal planting method had a significant effect on root number, and produced greater root length and dry weight of cassava than those of vertical planting method. Shoot and root growth developed different responses to planting method regardless of the cassava’s genotypic variations.